Vpliv štartne številke na rezultat vrhunskih tekmovalcev v alpskem smucanju - Lesnik, B.; Podovsovnik Axelsson, E.; Supej, M. (Kinesiologia Slovenica, 2013)
The study aimed to establish whether there is a relationship between competitors` start numbers and the times they achieved in individual course sections in a Slalom competition at the Europa Cup. The study included the top 15 ranked competitors in the first run who had been drawn for the starting order. The course was divided into eight sections and the times were measured for each section separately and for the entire course using computer-aided video analysis. The coefficient of variation (CV) showed that the differences between the competitors in terms of achieved times were larger mainly on the steeper sections of the competition course (CVPT/1 = 11.3%; CVPT/5 = 12.5%; CVPT/6 = 15.9%; CVPT/7 = 17.7%). This was also confirmed by the calculation of correlations among the achieved times in eight course sections and the final achieved time (S1: Sig. = 0.01; S2: Sig. = 0.00; S5: Sig. = 0.00; S6: Sig. = 0.01). In the steeper course sections, the correlations between the start numbers and the achieved times in individual course sections were also statistically significant (S1: Sig. = 0.029; S5: Sig. = 0.055). We can conclude based on the results that the influence of the start number can be observed already with the competitors who started first, and that the start number significantly influences a competitor`s final ranking, especially in the steeper course sections. This also applies to the conditions where the course has been hardened and prepared for competition.